Targeting aid to the needy and deserving: nothing but promises? - Peter Nunnenkamp; Rainer Thiele (The world economy, 2006)
By reallocating aid to where it is needed most and where a productive use is most likely, donors could help alleviate poverty in developing countries. The rhetoric of donors suggests that this insight has increasingly shaped the allocation of aid. We assess the poverty and policy orientation of bilateral and multilateral aid in different ways. In addition to presenting stylized facts based on bivariate correlations, we apply a Tobit model that captures both altruistic and selfish donor motives. We find little evidence supporting the view that the targeting of aid has improved significantly. Most donors provide higher aid to relatively poor countries, but so far the fight against poverty has not resulted in a stronger focus on the most needy recipients. The estimation results reveal that the policy orientation of aid critically depends on how local conditions are measured. Applying the widely used Kaufmann index on the quality of institutions, almost all donors failed to direct aid predominantly to where local conditions were conducive to a productive use of inflows. The response of donors to changing institutional and policy conditions in recipient countries turns out to be fairly weak. In particular, we reject the proposition that multilateral aid is more targeted than bilateral aid in terms of rewarding poor countries with better policies and institutions.
Keywords: F35; 330; bilateral aid; multilateral aid; fight against poverty; economic policy assessment; quality of institutions; Entwicklungshilfe; Entwicklungskooperation; Armutspolitik; Wirtschaftspolitische Wirkungsanalyse; Entwicklungsländer